Research of influence of random change of annular seal parameters on efficiency of centrifugal pump - Tarasevych, Yuliia; Savchenko, Ievgen; Sovenko, Nataliia; Savchenko, Anna (Eastern-European Journal of Enterprise Technologies, 2016)
Development of reliable methods of increasing of centrifugal pump efficiency is a very actual scientific and practical problem. One of ways to increase reliability and efficiency of centrifugal pump is an improvement of constructions of annular seals of running part and methods of their calculation. Now in engineering practice several approaches to research of complicated spiral flow of liquid in the small gaps of annular seals are used. Divergences in the conclusions of researchers are likely to be linked with assumptions that are accepted when solving nonlinear equations of non-stationary motion of liquid in the gap of annular seal. It is necessary to mark that divergences between the calculation values of hydrodynamic characteristics of annular seals and rotor-dynamic characteristics of pump that arise during exploitation are first of all possible to explain by the absence of account of possible change of geometrical parameters of the annular seals, caused by the accepted tolerances in the calculations. Using of probabilistic methods of calculation with existent statistical information got on the stages of design and operating of centrifugal pumps will allow to forecast reliability and efficiency of centrifugal pumps taking into account influence and changing of basic operating factors. Determination of influence of random change of annular seal parameters on flow-rate characteristics and volume efficiency of centrifugal pump is the goal of this research. Dependences to determinate the flow-rate of liquid through the annular seal are got by solving the problem of liquid flow in a cylindrical channel with taking into account the influence of random factors. Influence of random variations of basic geometrical and regime parameters of annular seal on efficiency pump is considered. It is shown on the example of cantilever pump with one impeller, that its efficiency can substantially (up to 1 %) decrease under exploitation. This decrease can be higher in case when pump has more stages.